Determinants of adoption and intensity of improved faba bean cultivars in the central highlands of Ethiopia: a double-hurdle approach - Yehuala Kassa; Almaz Giziew; Dereje Ayalew (CABI Agriculture and Bioscience, 2021)
Abstract Background Faba bean (Vicia faba. L) is the most important pulse crop both in area coverage and volume of annual production in Ethiopia. However, productivity in terms of yield in Ethiopia is still far below its potential. One important reason is that farmers are largely dependent on their local landraces. Despite the release of about 34 improved faba bean cultivars, farmers’ use of certified improved seeds is very low. This study, therefore, aimed to generate useful information on farmers’ adoption of improved faba bean cultivars by identifying factors that determine a farmer’s decision to use improved cultivars. Methods A multi-stage sampling technique was followed to select sample households. A cross-sectional household survey was used to collect data from 168 households that were randomly selected. Moreover, focus group discussions and key informant interviews were conducted. For data analysis, the Double-hurdle econometric model was employed. Results The results revealed that the majority, i.e., 77% of rural households depended on their local landraces. The adoption rate of improved faba bean seed at the household level was 23% which is very low. This low adoption rate was mainly due to a lack of access to improved seed and a lack of awareness about the improved cultivars. The results suggest that the decisions to adopt the improved cultivars and how much land to be covered appear to be explained by different processes. The double-hurdle econometric model result further revealed that while a farmer’s adoption decision is influenced by family size, farmers’ awareness about the existing improved cultivars, and extension contact, the intensity of adoption is determined by livestock holding and access to market information. Conclusion The result showed that most of the rural households were largely dependent on their local faba bean landraces which result in low yields at harvest. Therefore, it is suggested that the promotion of improved faba bean cultivars and improve farmers’ access to extension service and timely market information are the most decisive factors to be emphasized to improve the adoption of improved cultivars.